¿Influyó la teoría de libre comercio de Mises en la apertura económica colombiana? (1990-2005) (2011)
According to Mises, adopting free trade measurements allows countries to obtain beneficial results for its economy. Until 1991, Colombia was in a closed economic model, which was characterized by control of imports and exports through different mechanisms, both tariff and non tariff barriers. In that year, there were political and economic changes. The first is reflected in the issuance of a new Political Constitution that create new economic institutions and in proposing a scheme that integrates economic liberalization in a country committed to the global economy. The article aims to verify whether there is evidence that free trade measures adopted by Colombia between 1990 and 2005 are primarily or essentially to identify as part of the Mises theory, although in some countries in the implementation of economic policies can hardly be attributed to a single author, especially since in the decades before the study period there was a clear incidence of multilateral financial institutions and countries with high political ascendancy in the regional field, which directly influenced the design and implementation of economic policies. From the academic point of view the subject of the article is relevant, as an exercise approach to the economic theory of the Austrian school in general and Mises in particular. Timeliness and importance is given by the constant debate on international trade in a historical moment in which countries negotiate bilateral trade prolifically and the World Trade Organization is at a defining moment on the successful closing whether or not the Doha Round.